Multiple Supplemental Supernumerary Premolars: Unusual Presentation in a Nonsyndrome Patient - Ashwini Ramakrishna; Kiran B. Rajashekarappa (Hindawi Limited, 2013)
Supplementary teeth in the dental arch are a rare occurrence. Though they are mostly reported in association with syndromes they can also present in the absence of systemic pathology. This paper reports a case with multiple supernumerary teeth along with discussion of the frequency, types, complications, and management of such occurrence.